(untitled) (Perner’s Contacts, 2009)
Paper deals with the performance of transport in relation to environment, respectively to the air quality. It points out current problems, describes success solutions. The paper also analyse development of transport volume – key aspect of negative transport impact on environment, it deals with the concrete impacts of transport on air quality.